Obecność cudzoziemców na targowisku zlokalizowanym wokół Stadionu Dziesięciolecia z perspektywy kryminologicznej - Monika Szulecka (University of Warsaw, Centre of Migration Research (CMR), 2007)
– The scope of this paper is the market place located in the area of 10th-Anniversary Stadium in Warsaw, existing since 1989. Apart from the short characteristics and history of the object, in general the paper presents apects ot the market's functioning which refer to the multinational structure of peddlers and chich are connected with the issues of safety and legal order. To describe the functioning of the market from criminological perspective the results of field work carried out in 2004 and 2005 and partly press and official resources were used. Descriptions of the different phenomena presented in this paper are based on the subjective opinions of respondents on the unlawful behaviours, abillity to control them and the ways of responding to them, and also on the results of the observations carried individually.
Keywords: 330; Ambulanter Handel; Ambulanter Handel; Ausländer; Kriminalität; Warschau